Measurements of t(t)over-bar cross sections in association with b jets and inclusive jets and their ratio using dilepton final states in pp collisions at root s=13 TeV - Sirunyan, A. M. (2018)
The cross sections for the production of t (t) over bar b (b) over bar and t (t) over bar jj events and their ratio sigma(t (t) over bar b (b) over bar)/sigma(t (t) over bar jj) are measured using data corresponding to an integrated luminosity of 2.3 fb(-1) collected in pp collisions at root s = 13 TeV with the CMS detector at the LHC. Events with two leptons (e or mu) and at least four reconstructed jets, including at least two identified as b quark jets, in the final state are selected. In the full phase space, the measured ratio is 0.022 +/- 0.003 (stat) +/- 0.006 (syst), the cross section sigma(t (t) over bar b (b) over bar) bis 4.0 +/- 0.6 (stat)+/- 1.3 (syst) pb and sigma(t (t) over bar jj) is 184 +/- 6 (stat)+/- 33 (syst) pb. The measurements are compared with the standard model expectations obtained from a POWHEG simulation at next-to-leading-order interfaced with PYTHIA. (c) 2017 The Author. Published by Elsevier B.V.